2016
DOI: 10.3389/fphar.2016.00176
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antinociceptive and CNS Activities of Viscum orientale and High Sensitive Quantification of Bioactive Polyphenols by UPLC

Abstract: Viscum orientale Willd. (Loranthaceae) has long been used in traditional medicine to treat pain, neuropharmacological disorders and various forms of tumor but not yet been reported. The aim of this study is to rationalize the traditional medicinal use of this plant by evaluating the methanol extract of V. orientale leaves (MEVOL) for anti-nociceptive, CNS depressant and antioxidant activities and to quantify the bioactive polyphenols present in this plant. Five polyphenolic compounds namely gallic acid, vanill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Phenolics recently received much attention for its wide range of different function, including antioxidant ( Khatun et al, 2016 ; Xiao et al, 2016 ), anti-aging ( Zhuang et al, 2017 ), antimicrobial ( Alkan and Yemenicioǧlu, 2016 ), anti-diabetic ( Xiao and Högger, 2015 ; Xiao et al, 2015 ), anti-hyperlipidemia ( Sarma et al, 2016 ), hepatoprotective ( Ma et al, 2015 ), and anti-inflammatory effects ( Xiao, 2015 ). In addition, several researchers have reported the anti-tyrosinase and melanogenesis-inhibitory activities of various phenolic resources, including soybean ( Shukla et al, 2016 ), Ornithogalum narbonense ( Zengin et al, 2015 ), Mentha ( Fatiha et al, 2015 ), and wild edible mushroom ( Kaewnarin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolics recently received much attention for its wide range of different function, including antioxidant ( Khatun et al, 2016 ; Xiao et al, 2016 ), anti-aging ( Zhuang et al, 2017 ), antimicrobial ( Alkan and Yemenicioǧlu, 2016 ), anti-diabetic ( Xiao and Högger, 2015 ; Xiao et al, 2015 ), anti-hyperlipidemia ( Sarma et al, 2016 ), hepatoprotective ( Ma et al, 2015 ), and anti-inflammatory effects ( Xiao, 2015 ). In addition, several researchers have reported the anti-tyrosinase and melanogenesis-inhibitory activities of various phenolic resources, including soybean ( Shukla et al, 2016 ), Ornithogalum narbonense ( Zengin et al, 2015 ), Mentha ( Fatiha et al, 2015 ), and wild edible mushroom ( Kaewnarin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…MEAM leaves were examined for antioxidant activity using two usually acknowledged techniques: DPPH and ferric-reducing power analysis. Of note, it was determined that plant extractives reduced the stable DPPH radical content and minimized color changes due to the presence of antioxidant properties in samples [30]. The extract showed notable (p < 0.001) scavenging activity at the highest concentration (500 µg/mL) as compared with ascorbic acid, whereas the IC 50 value of the standard and crude extracts were 35.04 and 99.00 µg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of Viscum species on the central nervous system (CNS) is differential, and it was reviewed by Szurpnicka et al (2019) In vivo studies on mice and rats showed that Viscum species exhibited antiepileptic (Amabeoku et al 1998;Geetha et al 2010Geetha et al , 2018Gupta et al 2012;Tsyvunin et al 2016), sedative (Gupta et al 2012;Khatun et al 2016;Kumar et al 2016), analgesic (Orhan et al 2006;Khatun et al 2016), antianxiety, antidepressant, hypnotic, anti-stress (Kumar et al 2016) and antipsychotic activity (Gupta et al 2012) (Table 2). Several studies have proposed that the CNS activity of mistletoe is mediated by GABA (γ-aminobutyric acid) receptors.…”
Section: Neuropharmacological Activitymentioning
confidence: 99%
“…Numerous mistletoe extracts and isolated lectin showed radical-scaveging activity and protective effects against oxidative stress induced by free radicals, nitric oxide and superoxide anion (O 2 − ) (Sengul et al 2009;Papuc et al 2010;Kim et al 2010Kim et al , 2016Kusi et al 2015). It was studied that the activity of the more polar extracts was higher in different antioxidant mechanism and might result from high level of phenolic and flavonoid compounds (Orhan et al 2014;Khatun et al 2016;Pietrzak et al 2017). Furthermore, antioxidant activity of Viscum species depends on host tree (Vicas and Prokisch, 2009;Vicas et al 2011;Orhan et al 2014;Pietrzak et al 2017) and the time of harvest (Önay-Uçar et al 2006).…”
Section: Antioxidative Activitymentioning
confidence: 99%